Impacts of Hot Climate Conditions in Brazil: A Comprehensive Scientific Study - Delmo Da Silva (Global Writing Academica Researching & Publishing, 2023)
Brazil, a vast and ecologically diverse nation in South America, has been witnessing significant changes in its climate patterns over the past few decades. The rise in global temperatures due to anthropogenic activities has led to an increase in hot climate conditions in Brazil, impacting various aspects of its environment, economy, and society. This scientific study aims to provide a comprehensive analysis of the effects of hot climate conditions in Brazil, considering its geographical, ecological, and socio-economic dimensions.